Gamification in a textbook for Brazilian learners of English - Franco, Claudio de Paiva (BELT - Brazilian English Language Teaching Journal, 2022)
Gamification, i.e. the use of game design elements in non-game settings, has attracted an increasing academic interest with numerous research papers having been published on the application and evaluation of gamification in education. The strenuous effort to introduce innovation to textbooks and improve student engagement in the classroom has allowed gamification to gain ground in English language teaching. This article aims to present and discuss the strategies implemented to gamify a textbook for young Brazilian learners of English. In addition, it also intends to contribute to materials writing by describing some game design principles. Pedagogic and design implications stemming from the strategies adopted in the examined textbook include providing a variety of game design elements on varying levels of abstraction (game interface design patters, game design patterns and mechanics, game design principles and heuristics, and game models). Finally, the text shares some reflections on the importance of creating a student-centred learning environment based on meaningful gamification.